All Days 2008
DOI: 10.2118/115200-ms
|View full text |Cite
|
Sign up to set email alerts
|

Model for Transient Temperature and Pressure Behavior in Commingled Vertical Wells

Abstract: Multilayer transient testing is designed for determining individual layer properties (permeability and skin) for multiple layers commingled in a well. Traditional multilayer transient testing requires a combination of rate profiles from production log and transient rate and pressure measurements acquired at multiple surface rates. This method can be time consuming and may involve significant errors depending on the accuracy of the transient flow rate measurements. Today, many wells are equipped with downhole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Rate validation in integrated-asset modeling is a case in point. In contrast, temperature measurements have not found routine usage, but are gaining increased attention in connection with transientpressure testing (Sui et al 2008;Duru and Horne 2008;Izgec et al 2007;Hasan et al 2005;Kabir et al 1996), downhole flow profiling Nath et al 2007;Johnson et al 2006;Ouyang and Belanger 2006), and flow-rate estimation (Izgec et al 2009;Kabir et al 2008). This paper shows that both pressure and temperature responses at the tubinghead and annuli are strongly related to flow rates and that these measured values can be used to alert the operator of possible APB.…”
Section: Introductionmentioning
confidence: 95%
“…Rate validation in integrated-asset modeling is a case in point. In contrast, temperature measurements have not found routine usage, but are gaining increased attention in connection with transientpressure testing (Sui et al 2008;Duru and Horne 2008;Izgec et al 2007;Hasan et al 2005;Kabir et al 1996), downhole flow profiling Nath et al 2007;Johnson et al 2006;Ouyang and Belanger 2006), and flow-rate estimation (Izgec et al 2009;Kabir et al 2008). This paper shows that both pressure and temperature responses at the tubinghead and annuli are strongly related to flow rates and that these measured values can be used to alert the operator of possible APB.…”
Section: Introductionmentioning
confidence: 95%
“…Several recent studies attempted to investigate the potential of analyzing temperature measurements to characterize multilayer reservoirs. Sui et al (2008) presented a numerical model to evaluate the individual layer permeability and skin from transient temperature measurements of a commingled production well penetrating a multilayer gas reservoir. Under the condition of no layers communication, they found that the temperature response is sensitive to the damaged zone radius and permeability.…”
Section: Introductionmentioning
confidence: 99%
“…They relied on classical wellbore physical models 24,25,26 or on computational flow dynamics 27 . A recent model of a flowing compressible reservoir was used to show that the (simulated) temperature response could give detailed information on the near-wellbore structure 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis tools developed for this work required research on mathematical and numerical temperature description for wellbores 32,33 and flowing reservoirs 28,34,35,36 . The complexity of the supporting equations dictated that reservoir temperature models were solved for either the steady-state 34 or pseudo-steady-state 36 situations (with reservoir heat transfer coefficients (HTC) taken from other studies).…”
Section: Introductionmentioning
confidence: 99%